1978
DOI: 10.1016/0035-9203(78)90169-4
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and ecological aspects of schistosomiasis mansoni in the valley of the Paraíba do Sul river (São Paulo State, Brazil) I. Natural infection of small mammals with Schistosoma mansoni

Abstract: Small mammals naturally infected with Schistosoma mansoni were studied in the valley of the Paraíba do Sul river (São Paulo State, Brazil). 192 animals of 12 species were examined post mortem. Cavia aperea, Holochilus brasiliensis leucogaster, Nectomys squamipes squamipes, Oryzomys nigripes eliurus and Zygodontomys brachyurus were found infected. Most schistosome eggs found in the faeces were mature but no eggs were found in the faeces of C. aperea although adults were recovered. In the other infected animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

1980
1980
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
6
0
2
Order By: Relevance
“…The great variation in the number of excreted eggs observed in this study was similar to results found in naturally infected N. squamipes (Carvalho 1982), Holochilus brasiliensis leucogaster (Dias et al 1978) and in wild African rodents (Sène et al 1996).…”
Section: Discussionsupporting
confidence: 88%
“…The great variation in the number of excreted eggs observed in this study was similar to results found in naturally infected N. squamipes (Carvalho 1982), Holochilus brasiliensis leucogaster (Dias et al 1978) and in wild African rodents (Sène et al 1996).…”
Section: Discussionsupporting
confidence: 88%
“…Previous publications have described that some rodents can participate in the S. mansoni cycle but are unable to maintain an infection independent of man (Dias et al 1978). Studies should be conducted to investigate the participation of small wild rodents as an aggravating factor for maintenance of residual transmission in Pedro de Toledo.…”
Section: Discussionmentioning
confidence: 99%
“…The potentiality of Holochilus sp. to act as wild reservoir of S. mansoni was demonstrated by their ability to eliminate viable eggs in feces in a natural environment (Dias et al, 1978) and by their ability to complete the parasite cycle without human presence in semi-natural conditions, using Biomphalaria glabrata as an intermediary host (Carvalho et al, 1976). …”
Section: The Most Important Species Of Reservoir: Water-ratsmentioning
confidence: 99%
“…The emission peak during the day would be more related to human infection, as this is the time of greatest activity for the local people and of increased contact with contaminated water bodies, and the crepuscular peak could be related to infection in rodents, as they have twilight/nocturnal activity ( Fig. 9 and Previous studies have attempted to show differences between rodents and human S. mansoni strains through the following factors: external morphology of adult worms , pathogenicity in mice (Bastos et al, 1984, Silva & Andrade 1989, compatibility with snails (Bastos et al, 1984;Dias et al, 1978), sensitivity to drugs www.intechopen.com (Souza et al 1992) and iso-enzyme patterns (Oliveira, 1996). These biological differences, coupled with the existence of two different patterns of cercariae emission (diurnal and crepuscular / nocturnal), led to the hypothesi s t h a t t h e r e c o u l d b e d i f f e r e n c e s a t t h e molecular level between the human and rodent strains and between different geographical regions (Gentile & Oliveira, 2008).…”
Section: On a Regional Scalementioning
confidence: 99%